Craving among individuals with stimulant use disorder in residential social model-based treatment – Can exercise help?. (1st February 2022) - Salem, Bilal A.; Gonzales-Castaneda, Rachel; Ang, Alfonso; Rawson, Richard A.; Dickerson, Daniel; Chudzynski, Joy; Penate, Jose; Dolezal, Brett; Cooper, Christopher B.; Mooney, Larissa J.
Abstract: Background: In a randomized controlled 8-week trial, we examined the efficacy of aerobic and resistance exercise in reducing craving for methamphetamine (MA) among individuals with MA-use disorder during residential treatment. Methods: Individuals with MA use disorder (138) who were newly enrolled in residential treatment volunteered for random assignment to either an 8-week exercise intervention (EX) or health education control (HE), with both conditions meeting 3 times weekly; 3 dropped out of the trial, bringing the analysis sample to 135. The majority of participants were male (80%), and 48% were Latino/Hispanic. The mean age of the sample was 31.7 ( SD = 6.9) years. Using multivariate mixed models, differences between conditions were examined in: (1) craving for MA, measured by self-reported ratings on a Visual Analog Scale over the 8-week trial and, (2) MA use, measured by self-report and urine drug screens at baseline and 30 and 60 days after discharge from the 8-week study. Results: Results revealed significantly lower craving scores among the participants in the EX group than those in the HE group over the 8-week trial (median daily craving score for EX = 13.5, for HE = 21.8; p = .009). In addition, participants with less craving during treatment had significantly lower rates of MA use after discharge than participants with high craving measured at 30-days (p = .004) and 60-days post-discharge (p < .001). Conclusions: Results support the utility of incorporating a structured exercise program for individuals with MA-use disorder to reduce craving and improve MA-use outcomes. Highlights: Exercise significantly reduced craving during treatment for methamphetamine use. Participants with less craving during treatment had less MA use after discharge. Exercise may be a useful intervention for people in treatment for MA use disorder.